ALISIS VARIABEL YANG MEMPENGARUHI TINGKAT PENGEMBALIAN KREDIT UMKM PADA PROGRAM KEMITRAAN DAN BINA LINGKUNGAN (STUDI PADA PT. PELABUHAN INDONESIA III SURABAYA) - Yana Respati Dewi; Siti Aisjah (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
This research purposed to know the repayment credit on partnerhip and enviroment development program in PT Pelabuhan Indonesia III. This study measure influence variabel of loan amount, interest rate, monthly installments and and length of time against repayment credit. This study uses explanatory quantitative method. The data used on this study is primary data obtained from interview section and secondary data obtained from PT Pelabuhan Indonesia III. The result show that during last four years repayment credit was low. Today, from outcome of SPSS application sees that loan amount, interest rate, monthly installments and and length of time variabels has a leverage againts repayment credit as a simultaneous. But as a partial, only an interest rate did not has a significant influence against repayment credit. It also known that loan amount is the most influential variabel against repayment credit. Ultimate causes low level of repayment credit is about lack of awareness of partners to pay its obligations on the loan granted. Besides, theres no punishmens for partners who not repaid their debt on time. Keywords : Repayment credit, Partnership and Enviroment Development